How the worst moments in our lives make us who we are | Andrew Solomon (TEDx Patras, 2014)
: Πρόκειται να παρακολουθήσετε την εξωτερική σας εξωτερική εξωτερική εξωτερική εξωτερική εξωτερική εξωτερική εξωτερική εξωτερική εξωτερική εξωτερική εξωτερική εξωτερική πιστεύω ότι το σημαντικό ήταν εκεί, κάποια μεγαλύτερη πραγματικότητα περιμένει να βρεθεί. Αλλά μετά από την ώρα, έχω αισθάνει ότι η πραγματικότητα είναι αξιακότητα. Θεωρούμε το σημαντικότητα, αλλά μπορούμε να το καλύψουμε σημαντικότητα. Το τελευταίο μου κομμάτι μιλήθηκε για το πώς οι οικογένειες συμβουλεύονται με διάφορες τέτοιες δυνατότητες ή ανεξάρτησης, και μια από τις μητρές που εμβουλήσα, η οποία είχε δύο παιδιά με διάφορες τέτοιες δυνατότητες, μου είπε, «Ο κόσμος μας δίνει πάντα αυτές τις μικρές πραγματικές, όπως, «Γη δεν σας δίνει πάντα περισσότερα από τα οποία μπορείτε να αντιμετωπίσετε», αλλά οι παιδιά, σαν εμάς, δεν είναι προοδευμένοι ως έγγραφο, είναι έγγραφο, γιατί αυτό είναι αυτό που έχουμε σχεδόνει. Καταφέρνουμε αυτές τις επιλογές όλης τη ζωή μας. Όταν ήμουν δεύτερος βαθμός, ο Bobby Finkel είχε μια γιορτήρα, και έκανε όλους εμείς στη διάρκεια μας, αλλά εμένα. Η μητέρα ασφαλίθηκε ότι υπήρχε κάποια εξάσκηση, και την έκανε, κύριε Finkel, που είπε ότι ο Bobby δεν μου άρεσε και δεν μου ήθελε στο γιορτήριό του. Και εκείνη την ημέρα, η μητέρα με έκανε στο ζωο και έκανε για ένα κακό φιγγίστο. Όταν ήμουν δεύτερος βαθμός, ένας από τους παιδιτών μου στο γιορτήριο της σχολής μου με ονομάζε Πέρσι, ως κορυφαίος για το δημιουργικό μου. Και κάποιες φορές, εκείνος και το κορυφαίο του έκανε τη διάρκεια του γιορτήριου της σχολής, 45 λεπτά πάνω, 45 λεπτά πίσω. Πέρσι, Πέρσι, Πέρσι, Πέρσι. Όταν ήμουν δεύτερος βαθμός, η διεξιά μας είπε ότι όλοι οι μηχανικοί φιγγίστοι δημιουργούν φιγγίστοι, επειδή έχουν τραυματίσει το σφιγγίστο τους. Και εγώ εξακολουθούσα στη σχολή χωρίς να πηγαίνω στο καφετήριο, όπου θα έπαιξα με τις γυναίκες και θα ήθελα να το κάνω, ή θα έπαιξα με τους γυναίκες και θα ήθελα να είμαι ένας γυναίκος που θα έπαιξε με τις γυναίκες. Εγώ υπήρξα την παιδιά μου μέσα από ένα μικρό βαθμό και υπέροχο, but what I didn't know then and do know now is that avoidance and endurance can be the entryway to forging meaning. After you've forged meaning, you need to incorporate that meaning into a new identity. You need to take the traumas and make them part of who you've come to be, and you need to fold the worst events of your life into a narrative of triumph, evincing a better self in response to things that hurt. One of the other mothers I interviewed when I was working on my book had been raped as an adolescent and had a child following that rape, which had thrown away her career plans and damaged all of her emotional relationships. But when I met her, she was 50, and I said to her, do you often think about the man who raped you? And she said, I used to think about him with anger, but now only with pity. And I thought she meant pity because he was so unevolved as to have done this terrible thing. And I said, pity? And she said, yes, because he has a beautiful daughter and two beautiful grandchildren, and he doesn't know that, and I do. So as it turns out, I'm the lucky one. Some of our struggles are things we're born to, our gender, our sexuality, our race, our disability. And some are things that happen to us, being a political prisoner, being a rape victim, being a Katrina survivor. Identity involves entering a community to draw strength from that community and to give strength there, too. It involves substituting and for but, not, I am here, but I have cancer, but rather, I have cancer and I am here. When we're ashamed, we can't tell our stories, and stories are the foundation of identity. Forge meaning, build identity. Forge meaning and build identity. That became my mantra. Forging meaning is about changing yourself. Building identity is about changing the world. All of us with stigmatized identities face this question daily. How much to accommodate society by constraining ourselves and how much to break the limits of what constitutes a valid life. Forging meaning and building identity does not make what was wrong right. It only makes what was wrong precious. In January of this year, I went to Myanmar to interview political prisoners, and I was surprised to find them less bitter than I had anticipated. Most of them had knowingly committed the offenses that landed them in prison, and they had walked in with their heads held high and their heads held high, and they walked out with their heads still held high. Many years later, Dr. Mathida, a leading human rights activist who had nearly died in prison and had spent many years in solitary confinement, told me she was grateful to her jailers for the time she had had to think, for the wisdom she had gained, for the chance to hone her meditation skills. She had sought meaning and made her travail into a crucial identity. But if the people I met were less bitter than I had anticipated about being in prison, they were also less thrilled than I had expected about the reform process going on in their country. Mathida said, we Burmese are noted for our tremendous grace under pressure, but we also have grievance under glamour. She said, and the fact that there have been these shifts and changes doesn't erase the continuing problems in our society that we learned to see so well while we were in prison. And I understood her to be saying that concessions confer only a little humanity, where full humanity is due, that crumbs are not the same as a place at the table, which is to say, you can forge meaning and build identity, build identity and still be mad as hell. I've never been raped, and I've never been in anything remotely approaching a Burmese prison. But as a gay American, I've experienced prejudice and even hatred, and I've forged meaning, and I've built identity, which is a move I learned from people who had experienced far worse privation than I've ever known. In my own adolescence, I went to extreme lengths to try to be straight. I enrolled myself in something called sexual surrogacy therapy, in which people I was encouraged to call doctors prescribed what I was encouraged to call exercises with women I was encouraged to call surrogates, who were not exactly prostitutes but who were also not exactly anything else. . . My particular favorite was a blonde woman from the Deep South, who eventually admitted to me that she was really a necrophiliac and had taken this job after she got in trouble down at the morgue. . These experiences eventually allowed me to have some happy physical relationships with women, for which I'm grateful. But I was at war with myself, and I dug terrible wounds into my own psyche. We don't seek the painful experiences that hew our identities, but we seek our identities in the wake of painful experiences. We cannot bear a pointless torment, but we can endure great pain if we believe that it's purposeful. Ease makes less of an impression on us than struggle. We could have been ourselves without our delights, but not without the misfortunes that drive our search for meaning. Therefore, I take pleasure in infirmities, Saint Paul wrote in 2 Corinthians, for when I am weak, then I am strong. In 1988, I went to Moscow to interview artists of the Soviet underground, and I expected their work to be dissident and political. But the radicalism in their work actually lay in reinserting humanity into a society that was annihilating humanity itself, as in some senses, Russian society is now doing again. One of the artists I met said to me, we were entraining to be not artists, but angels. In 1991, I went back to see the artists I'd been writing about, and I was with them during the putsch that ended the Soviet Union, and they were among the chief organizers of the resistance to that putsch. And on the third day of the putsch, one of them suggested we walk up to Smolenskaya, and we went there, and we ranged ourselves in front of one of the barricades, and a little while later, a column of tanks rolled up. And the soldier on the front tank said, we have unconditional orders to destroy this barricade. If you get out of the way, we don't need to hurt you, but if you won't move, we'll have no choice but to run you down. And the artist I was with said, give us just a minute. Give us just a minute to tell you why we're here. And the soldier folded his arms, and the artist launched into a Jeffersonian panegyric to democracy, such as those of us who live in a Jeffersonian democracy would be hard-pressed to present. And they went on and on, and the soldier walked, and then he sat there for a full minute after they were finished and looked at us so bedraggled in the rain and said, what you have said is true, and we must bow to the will of the people. If you'll clear enough space for us to turn around, we'll go back the way we came. And that's what they did. Sometimes, forging meaning can give you the vocabulary you need to fight for your ultimate freedom. Russia awakened me to the lemonade notion that oppression breeds the power to oppose it, and I gradually understood that as the cornerstone of identity. It took identity to rescue me from sadness. The gay rights movement posits a world in which my aberrances are a victory. Identity politics always works on two fronts, to give pride to people who have a given condition or characteristic and to cause the outside world to treat such people more gently and more kindly. Those are two totally separate enterprises, but progress in each sphere reverberates in the other. Identity politics can be narcissistic. People extol a difference only because it's theirs. People narrow the world and function in discrete groups without empathy for one another. But properly understood and wisely practiced, identity politics should expand our idea of what it is to be human. Identity itself should be not a smug label or a gold medal, but a revolution. I would have had an easier life if I were straight, but I would not be me, and I now like being myself better than the idea of being someone else, someone who, to be honest, I have neither the option of being nor the ability fully to imagine. But if you banish the dragons, you banish the heroes, and we become attached to the heroic strain in our own lives. I've sometimes wondered whether I could have ceased to hate that part of myself without Gay Pride's technicolor fiesta, of which this speech is one manifestation. I used to think I would know myself to be mature when I could simply be gay without emphasis. There's still an outer world of homophobia that it will take decades to address. Someday, being gay will be a simple fact, free of party hats and blame. But not yet. A friend of mine, who thought Gay Pride was getting very carried away with itself, once suggested that we organize Gay Humility Week. It's a great idea, but its time has not yet come, and neutrality, which seems to lie halfway between despair and celebration, is actually the endgame. In 29 states in the US, I could legally be fired or denied housing for being gay. In Russia, the anti-propaganda law has led to people being beaten in the streets. Twenty-seven African countries have passed laws against sodomy, and in Nigeria, gay people can legally be stoned to death, and lynchings have become common. In Saudi Arabia recently, two men who had been caught in carnal acts were sentenced to 7,000 lashes each, and are now permanently disabled as a result. So who can forge meaning and build identity? Gay rights are not primarily marriage rights, and for the millions who live in unaccepting places with no resources, dignity remains elusive. I'm lucky to have forged meaning and built identity, but that's still a rare privilege, and gay people deserve more collectively than the crumbs of justice. And yet, every step forward is so sweet. In 2007, six years after we met, my partner and I decided to get married. Meeting John had been the discovery of great happiness and also the elimination of great unhappiness. And sometimes, I was so occupied with the disappearance of all that pain that I forgot about the joy, which was at first the less remarkable part of it to me. Marrying was a way to declare our love as more a presence than an absence. Marriage soon led us to children, and that meant new meanings and new identities, ours and theirs. I want my children to be happy, and I love them most achingly when they are sad. As a gay father, I can teach them to own what is wrong in their lives, but I believe that if I succeed in sheltering them from adversity, I will have failed as a parent. A Buddhist scholar I know once explained to me that Westerners mistakenly think that nirvana is what arrives when all your woe is behind you and you have only bliss to look forward to. But he said that would not be nirvana, because your bliss in the present would always be shadowed by the joy from the past. Nirvana, he said, is what you arrive at when you have only bliss to look forward to and find in what looked like sorrows the seedlings of your joy. And I sometimes wonder whether I could have found such fulfillment in marriage and children if they'd come more readily, if I'd been straight in my youth or were young now, in either of which cases this might be easier. Perhaps I could. Perhaps all the complex imagining I've done could have been applied to other topics. But if seeking meaning matters more than finding meaning, the question is not whether I'd be happier for having been bullied, but whether assigning meaning to those experiences has made me a better father. I tend to find the ecstasy hidden in ordinary joys, because I did not expect those joys to be ordinary to me. I know many heterosexuals who have equally happy marriages and families, but gay marriage is so breathtakingly fresh and gay families so exhilaratingly new, and I found meaning in that surprise. In October, it was my 50th birthday, and my family organized a party for me. And in the middle of it, my son said to my husband that he wanted to make a speech. And John said, George, you can't make a speech. You're four. (*Laughter*) Only Grandpa and Uncle David and I are going to make speeches tonight. But George insisted and insisted, and finally John took him up to the microphone, and George said very loudly, Ladies and gentlemen, may I have your attention, please? And everyone turned around, startled. And George said, I'm glad it's Daddy's birthday. I'm glad we all get cake. (*Laughter*) And Daddy, if you were little, I'd be your friend. (*Aww*) And I thought... Thank you. I thought that I was indebted even to Bobby Finkel, because all those earlier experiences were what had propelled me to this moment, and I was finally unconditionally grateful for a life I'd once have done anything to change. The gay activist Harvey Milk was once asked by a younger gay man what he could do to help the movement, and Harvey Milk said, Go out and tell someone. There's always somebody who wants to confiscate our humanity, and there are always stories that restore it. If we live out loud, we can trounce the hatred and expand everyone's lives. Forge meaning, build identity. Forge meaning, build identity. And then invite the world to share your joy. Thank you. (*Applause*) Thank you. (*Applause*) Thank you. (*Applause*) Thank you. (*Applause*)